Therapeutic effectiveness of three commercial anthelmintics against strongylids in buffalo calves (Bubalus bubalis) - David Uzcátegui; Víctor Gutiérrez; María Rodríguez; Andrea González; Alfredo Sánchez (Revista Científica)
Gastrointestinal parasites and their control in buffaloes (Bubalus bubalis) represent increasing production costs. To improve sanitary plans in buffalo herds, experimental field re-search was carried out to evaluate the efficacy of three commercial anthelmintics against strongylids parasites in buffalo calves. The effectiveness of the anthelmintics was estimated through faecal egg count (FEC) reduction percentage. The study was conducted in a buffalo system dedicated to milk and meat production with crossbreed animals (Murrah and Mediterranean breeds) in the South of Lake Maracaibo, Venezuela. Twenty-eight buffalo calves, naturally infected, with a parasite load ≥ 350 eggs per gram of faeces (EPG), and age between 2 and 3 months, with an average weight of 65.9 kgs, were selected. The animals were grouped into four treatments: T0 control without anthelmintic; T1 fenbendazole 10%, Intervet  laboratory, Brazil, at 5mg/kg orally; T2 ivermectin 1%, SIGMA laboratory, Venezuela, at 0.2 mg/kg subcutaneously; and T3 levamisole hydrochloride 22.3%, Valmor laboratory, Venezuela, at 4.5 mg/kg subcutaneously. The anthelmintics were applied in a single dose on day zero (0) of the research. A coprological diagnosis was performed prior to treatment and at 14 (A), 21 (B) and 28 (C) days after treatment. The faecal samples were examined by applying McMaster’s technique with saturated saline. Data was analyzed with descriptive statistics and the nonparametric Friedman test. The FEC reduction percentage was calculated for each anthelmintic. Moreover, the lower limit of the 95% confidence interval was calculated for each anthelmintic (low-CI95%). The mean EPG before treatment (BT) was 907.1 EPG, 978.6 EPG, 1057.1 EPG, and 921.4 EPG for T0, T1, T2, and T3, respectively. The mean of EPG during the evaluation of the different treatments showed significant variations (p<0.05): T1 in A (42.9), B (200) and C (178.6). For T2 in A (671.4), B (571.4) and C (964); and for T3 in A (41.7), B (92.9) and C (121.4). The FEC reduction percentage at times A, B and C at T1 was 97%, 81.1% and 84.7% and a low-CI 95% of 67%; for T2 it was 51.5%, 46% and 17.4% and a low-CI 95% of -7.2%; and for T3 it was 97%, 91.2% and 89.6% and a low-CI 95% of 82.9%. Conclusions are that T1 and T3 presented a mean of EPG at low levels (≤ 200) during the evaluated period in comparison to T2, which remained at a high level of infection (> 500). Furthermore, levamisole was most effective against strongylids. In the case of ivermectin, the FEC reduction percentage was less than 90% during the trial, resulting in a low-CI 95% of -7.2%, showing possible anthelmintic resistance.